CORONAVIRUS DISEASE 2019 (COVID-19) ON CHILD: A SYSTEMATIC RIVIEW - Wardani, Rafida Kusuma; Riono, Pandu (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
.In March 2020, WHO set the status of the 2019 Corona Virus pandemic. Significantly there is a surge in cases around the world. Of course, this not only has an impact on health, but on all areas until problems occur in the economy of various countries. Public Health also plays a role in helping control the COVID-19 pandemic by clinical trials for emergency vaccines in hopes of helping to control the spread of COVID-19 cases well. There are several groups that belong to the vulnerable category of pregnant women, elderly, people with comorbids and also groups of children who have not been able to get COVID-19 vaccination. Researchers are interested in conducting Systematic Review with the reason to know various clinical symptoms, risks and proportions of COVID-19 events in children that will certainly be very useful for the development of science. Results obtained from a study of 10 related article sources analyzed based on several sub-criteria such as symptoms, death, signs, age, prognosis and sex in Systematic Review are known that there are various clinical symptoms that arise in children with COVID-19 but fever and cough dominate, but COVID-19 symptoms in children tend to be milder than in adults. The conclusion that is found in children, especially younger children, tends to have many virus infections. It is possible that there is repeated exposure to the virus. The main limitation in this systematic research is that there is difficulty in reading the full text of some Chinese studies.